Concomitant production of gum, nut and peduncle in dwarf cashew tree explored under different levels of irrigation and fertilization - Lima, Reivany Eduardo Morais; de Araújo, Laíse Ferreira; Barros, Josivavia Rodrigues; Bezerra, Marlos Alves (Comunicata Scientiae, 2017)
The main goal of this innovator study was to evaluate if the gum extraction influences the production of nut and peduncle of precocious dwarf cashew tree grown under different water regimes and mineral nutrition. Adult trees of CCP-76 clone were submitted to water regimes: irrigated (100% da ETpc) and non-irrigated, and three fertilization levels with NK: 50%, 100% and 150% of the recommended for the crop nutrition. Additionally was added a treatment in which the gum was not extracted from plants (control). The extraction of gum was performed monthly during a period of 15 months, while the nut and peduncle were collected at the end of the cropping season, after the gum extraction period. The quality of the peduncle was determined by the soluble solids content (SSP). The production of gum in the first semester of the year followed an increasing trend on every three months, regardless the water regime. In the second semester, an interaction between the factors was observed, with irrigated plants producing more gum in higher fertilizer levels (100 and 150%), while in the non-irrigated conditions, the highest gum production occurred with the lower fertilization level (50%). The production of nut and peduncle were not affected by treatments or gum extraction. The highest contents of SSP was observed when the plants were irrigated.